Surgical Management of Giant Congenital Hairy Nevi Without Skin Graft or Other Methods of Closure - Sukasah, Chaula L; Supit, Laureen (Jurnal Plastik Rekonstruksi, 2012)
Congenital hairy nevus refers to pigmented skin lesion presents at birth. Giant hairy nevus (GHN) is disfiguring and carries a great emotional distress on the patient and family. It also imposes a higher risk for developing malignant melanomas and other tumors. The management of GHN depends on the lesions’ size, location and its propensity to become malignant. When surgery is indicated, the simplest approach is a staged serial excisions. The longstanding challenge is in reconstructing the raw surface defect, especially if large. A case of congenital GHN on the trunk, abdomen and bilateral upper thighs was presented and the data was taken from the medical record from the Plastic and Reconstructive Surgery Division of Cipto Mangunkusumo Hospital. Patient was managed surgically with a technique similar to dermabrasion, by scalpel instead of dermabrator, to peel the skin in partial-thickness. In each surgery, not more than 10% of the total body surface area was excised and left to heal secondarily. Compression was used to reduce risk of hypertrophic scar formation. Subsequent operation was ideally 3 weeks apart, to allow for the excised surface to epithelialize and the body to return to homeostasis. Although visible, the patient’s family prefer the resulting scar than the initial lesion, because the skin is lighter, hairless, and less frightening. At two-years follow up, the patient still refuse further operation due to economical and social issues.